The Formula of the formula and its role in determining the meaning (An applied study on the poetry of Abu Tammam Al-Ta'i) - صفية, وحيد; حاج حسين, هلال رياض (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
It is the theory of clues presented by Tammam Hassan in his book (Arabic language meaning and structure) is a basic building block for the restructuring of Arabic grammar in its entirety And that is on the basis of meaning first Hassan saw that the Arabic linguistic studies were characterized by the characteristic of orientation towards the building in the first place and did not intend the meaning except accordingly and timidly. Through this theory, Tamam Hassan was able to rearrange ideas and linguistic theories, in contradiction to what was settled on from the era of Sibawayh to his time. Among the clues that Tamam Hassan spoke about is the expression of the form, whose importance lies in inferring the structure of the structure and determining the syntactic and analytical functions of the sentence. Based on that, our research came to talk about this context that plays a prominent role in the composition by defining the meaning. We have tried to apply the data of the context of the formula to the poetry of Abu Tamam al-Ta'i, which is characterized by eloquence, strength and generosity.